Intention towards mobile multimedia message (MMS) advertisements - Jayasooriya, T.S.; Shivany, S.; Sathana, V. (My University, 2019)
Advanced technology plays a significant role in analysis of consumers’ psychology and their changed behavior towards purchasing any particular product. There are currently many different ways of marketing communications, by which marketers can reach their target audience. At present, the consumers are living in such an environment where they can get the information about a product or service from the various available media vehicles. Presence of numerous media vehicles in the advertising world has created an advertising clutter, reducing the effectiveness of advertising. That is why marketers are looking for innovative Medias and methods for advertising, which has yet not been saturated, and mobile multimedia message advertising is one of them. Mobile advertisements allow the marketers to approach the customers’ indistinctive way, but, there arises a question that how does a consumer observe this innovative way of advertising. The present study attempts to examine consumer attitude towards mobile advertising intention and the various factors that influence their intention. This study mainly relies on primary data collected through validated questionnaire. The study will be beneficial for the marketers to gain an insight of consumer attitude and their intention for mobile advertising and to define the appropriate strategies targeting them accordingly. Empirical study was conducted to collect the primary data using a questionnaire as a tool in order to test the hypotheses. The questionnaire was distributed to 200 respondents who were randomly selected from the population. The findings proved that there is a relationship between independent variables (i.e., entertainment, informative, irritation, credibility and personality) and the dependent variable (consumer intention toward mobile multimedia message advertising) based on several reasons discussed thoroughly in this research.
Keywords: Advertisements; Attitude; Customer intention Mobile Multimedia Message advertising